Behavior of structurally divergent -tubulin isotypes during Drosophila embryogenesis: evidence for post-translational regulation of isotype abundance. - Theurkauf, W.E. (Developmental Biology, 1992)
Two major alpha-tubulin isotypes are present during Drosophila embryogenesis: an evolutionarily divergent maternal isotype that is synthesized only in the ovary and deposited in the oocyte and a highly conserved constitutive isotype that is both maternally supplied and zygotically synthesized. A maternal isotype-specific antibody and a monoclonal antibody that recognizes both the maternal and constitutive isotypes were characterized and used to determine the distribution and abundance of alpha-tubulins during embryogenesis. Both isotypes are abundant and assemble into all classes of microtubules from the syncytial blastoderm stage until completion of germ band retraction. During subsequent development, however, the maternal isotype is retained only in the developing CNS, and later in a subset of connective fibers within the CNS. In contrast, total alpha-tubulin levels remain high in essentially all tissues throughout embryogenesis, indicating that most tissues selectively accumulate the constitutive isotype. To determine if selective accumulation of the constitutive isotype requires zygotic synthesis of this protein, mutant embryos that do not contain functional constitutive alpha-tubulin genes were examined. In these embryos, as in wild type, the maternal isotype decreases to background levels in tissues that retain high levels of the constitutive isotype. The constitutive isotype therefore appears to be more stable than the maternal isotype in most tissues. Differences in isotype stability may play an important role in determining the developmental pattern of isotype accumulation in Drosophila embryos.